OP0085-HPR Comparison of Patient and Practitioners Perceptions of Nurse-Led and Consultant-Led Rheumatology Outpatient Consultations. (10th June 2014) - Vinall, K.A.; Madill, A.; Firth, J.
Abstract : Background: This study is concurrent to a RCT of effectiveness for RA patients attending nurse-led Rheumatology clinics (NLC). Whilst the RCT compared patient outcomes (Ndosi et al. 2013), this abstract reports differences in perceptions of NLC and consultant-led clinics. Objectives: The purpose of the analysis was to compare and contrast practitioner and patient perceptions of the consultation. Methods: 31 semi-structured interviews were undertaken: 8 clinical nurse specialist (CNS); 8 consultant rheumatologists (CR) and their patients (8 and 7 respectively) at 9 rheumatology outpatient departments (UK). Interviews were audio recorded, transcribed in verbatim and analysed (KV). Thematic analysis followed the recommendations of Braun & Clarke (2006). Patient and practitioner interviews were analysed separately and then compared and contrasted. This abstract reports on the comparisons made between patient and practitioner interviews where communality between themes was identified. Results: Practitioner themes; "setup of clinics"; "running to time" and patient themes; "centre/structure factors"; "personal characteristics of practitioner" were compared. Both CNS and CR describe differences in clinics at an institutional level with CNS having more influence over "setup" such as booking patients' appointments themselves. Patients highly value this continuity in appointments showing that the "setup" described by practitioners impacts upon patients' perceptions. Patients describe the importance of "someone keeping an eye on things" which they attribute more to the CNS. The practitioner interviews offer insight that this is often due to "setup of clinics" but is perceived by patients as relating to the "personal characteristics of the practitioner". All participants acknowledge contextual factors as important to the quality of care given i.e. "running to time". However, patients' attribute this to "personal characteristics of practitioners" irrespective of role (CNS or CR) as demonstrating that they have "time for you". Thus whilst they appear to identify similar quality standards, in fact what is described is not the same as that described by practitioners, but of feeling valued and important within the consultation. Conclusions: Seeing the same practitioner and familiarity with patients' personal circumstances are viewed highly by patients in establishing rapport and providing emotional support. What the practitioner interviews add is that many of the factors are dictated in "setup of clinics" and differs according to CNS or CR which consequently impacts upon the patients evaluation of practitioners. The findings relating to 'running to time' are consistent with those of Donovan & Blake (2000) that "it was the perception of having symptoms and problems acknowledged that seemed to matter, not time itself". References: Ndosi, Mwidimi, et al. The outcome and cost-effectiveness of nurse-led care in people with rheumatoid arthritis: a multicentre randomised controlled trial. Annals of the rheumatic diseases (2013). Braun, Virginia, and Victoria Clarke. Using thematic analysis in psychology. Qualitative research in psychology 3.2 (2006): 77-101. Donovan, Jenny L., and David R. Blake. Qualitative study of interpretation of reassurance among patients attending rheumatology clinics: "just a touch of arthritis, doctor?". BMJ 320.7234 (2000): 541-544. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4347